EDUKASI SAMPAH DAN PENGELOLAAN SAMPAH KEPADA SISWA KELAS III SDIT AL-BIDAYAH BITUNG - Tanjung Putri, Elsari; Apriani, Ita (Jurnal Abdimas Bina Bangsa, 2025)
School is one of the public facilities that can produce waste every day from activities carried out by students and teaching staff. Community service activities serve as a platform for transferring knowledge and skills through community education programs. The aims of this activity is to provide education for students and teachers about waste (household waste and marine debris) and its management. The process of conducting activities involves the preparation phase, the implementation phase through socialization and counseling, and the evaluation phase. Data analysis is done using descriptive analysis. The results showed that the activity was going well with enthusiastic students and active discussions with the lecturer team. There was a significant increase in the percentage of people with knowledge and understanding of waste material and its management. The percentage of correct answers in the pretest was only 3%, but increased to 83% after socialisation (posttest).